2022
DOI: 10.1128/mbio.02294-22
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Enterococcal Cell Envelope during Surface Penetration Promotes Intrinsic Resistance to Stress

Abstract: Enterococcus faecalis inhabits the GIT of multiple organisms, where its establishment could be mediated by the formation of biofilm-like aggregates. In susceptible individuals, this bacterium can overgrow and breach intestinal barriers, a process that may lead to lethal systemic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 123 publications
(192 reference statements)
0
11
0
Order By: Relevance
“…S1 and Table 2, ESI†) using mechanisms available to other Gram-positive bacteria, clearly suggesting that the peptide's activity against these bacteria may show a more limited spectrum. 55,71,142–148…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 and Table 2, ESI†) using mechanisms available to other Gram-positive bacteria, clearly suggesting that the peptide's activity against these bacteria may show a more limited spectrum. 55,71,142–148…”
Section: Discussionmentioning
confidence: 99%
“…10A) In support of this suggestion, Lys-PG has also been detected in the CM of other bacteria 55,[139][140][141] and appears to inhibit binding by AMPs in resistance mechanism with similarities to that mediated by the lipid in S. aureus. 55,71,[142][143][144][145][146][147][148] Interestingly, in what seems to be an evolutionary response, some creatures appear to produce anionic AMPs that bind Lys-PG to overcome S. aureus resistance mechanisms and promote their antibacterial action. 149 The weak affinity of M5-NH 2 for the CM of S. aureus appeared to limit rather than completely abolish the ability of the peptide to interact with these membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Despite its nonmotile nature, we have demonstrated that this bacterium can penetrate semisolid agar media and epithelial cell monolayers 18–20 . Exploiting this system, we observed that while some enterococcal cells remain on the agar surface, forming an external colony, others migrate within, resulting in a distinct “colony-print” formation within the semisolid medium 18,20 . Both external and penetrating enterococci exhibited unique genetic programs, conferring fitness advantages to the invading cells, including increased antibiotic resistance 20 .…”
mentioning
confidence: 97%
“…Exploiting this system, we observed that while some enterococcal cells remain on the agar surface, forming an external colony, others migrate within, resulting in a distinct “colony-print” formation within the semisolid medium 18,20 . Both external and penetrating enterococci exhibited unique genetic programs, conferring fitness advantages to the invading cells, including increased antibiotic resistance 20 . Moreover, our research has unveiled that successful E faecalis agar penetration requires the formation of multicellular aggregates and the synthesis of extracellular polysaccharides, particularly highlighting the role of polyGlcNAc (an exopolysaccharide composed of N -acetylglucosamine) 18,19 .…”
mentioning
confidence: 99%